Technical NEMA NU2–2018 Performance Assessment of Time-of-Flight-Integrated Digital PET-CT System - Singh, Manoj Kumar; Agarwal, Krishan Kant; Vishwakarma, Manish; Patel, Hemant (World Journal of Nuclear Medicine, 2024)
Aim The objective of this study includes the NEMA (National Electrical Manufacturer Association) NU2–2018 performance evaluation of the uMIvista PET-CT (positron emission tomography-computed tomography) system.Methods The latest NEMA NU2–2018 guidelines have been followed for the evaluation of performance parameters of this PET-CT scanner: axial, tangential, and radial spatial resolution, sensitivity, counting losses, scatter, randomness, random and counting loss correction, image quality, time and energy resolution, image uniformity, and image registration alignment post installation of country first uMIvista PET-CT.Results The measured NEMA sensitivity of the uMIvista PET scanner was 12.053 cps/kBq. The spatial resolutions of the PET were measured as tangential, radial, and transaxial spatial resolutions at 10 mm, with 3.01 mm, 2.95 mm, and 2.93 mm, respectively; at 100 mm, with 3.17 mm, 3.42 mm, and 3.05 mm, respectively; and at 200 mm, with 3.65 mm, 4.54 mm, and 3.17 mm, respectively, at full-width half-maximum (FWHM); while at full-width tenths-maximum (FWTM), the values at 10 mm were 5.79 mm, 5.57 mm, and 5.69 mm, respectively, and at 100 mm were 5.59 mm, 5.96 mm, and 5.91 mm, respectively. The measured time-of-flight (TOF) timing resolution was 302.294 ps and the measured energy resolution was 11.76% with FWHM and FWTM.Conclusion The NEMA NU2–2018 performances of this TOF-integrated digital PET-CT system are extremely good in all parameters.
Keywords: digital PET-CT; NEMA; NEMA NU2–2018; PET; PET-CT; resolution; sensitivity; TOF